Research Procedures and Validity Criteria for Sanad Hadith - Prihambodo, Dimas (Research and Development Institution, Darussalam Institute for Islamic Studies, 2023)
Islam as ad-din and civilization are big themes in this era. This can be seen in the emergence of works that attempt to explain this, written by Indonesian scholars such as Nurcholish Madjid, Syeid Muhammad Naquib al-Attas, Kuntowijoyo, M. Amin Abdullah, and others. This article attempts to revive Islamic studies in the discipline of 'ulum al-hadith regarding the criteria for the validity of hadith sanads and research steps. The results of this writing show that sanad is an arrangement in the form of levels of narrators of a hadith. Broadly speaking, the criteria for rijalu sanad are fair and careful. Research also found that the steps for researching hadith sanads can be formulated into several steps, including takhrij hadith, i'tibar hadith, research using the sanad scheme, researching ar-Ruwat dates and researching al-jarhu wa at-ta'dil.